2013
DOI: 10.1007/978-1-4614-7411-1_44
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling Blood Flow and Metabolism in the Piglet Brain During Hypoxia-Ischaemia: Simulating pH Changes

Abstract: We describe the extension of a computational model of blood flow and metabolism in the piglet brain to investigate changes in neonatal intracellular brain pH during hypoxia-ischemia (HI). The model is able to simulate near-infrared spectroscopy (NIRS) and magnetic resonance spectroscopy (MRS) measurements obtained from HI experiments conducted in piglets. We adopt a method of using 31P-MRS data to estimate of intracellular pH and compare measured pH and oxygenation with their modelled counterparts. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These questions could be addressed by combining advanced optics with multimodal monitoring and imaging. Approaches integrating information from time-resolved spectroscopy, imaging, and multimodal neuromonitoring by optical and physiological modeling are feasible and may hold the key to predicting how cortical physiology manifests in NIRS optics 36. NIRS reflects considerable physiological complexity, and model-based physiological interpretation37,38 of NIRS might therefore usefully be used to address influence of other confounding factors such as carbon dioxide tension,39 oxygenation,40 and cerebral metabolic rate 41.…”
Section: Discussionmentioning
confidence: 99%
“…These questions could be addressed by combining advanced optics with multimodal monitoring and imaging. Approaches integrating information from time-resolved spectroscopy, imaging, and multimodal neuromonitoring by optical and physiological modeling are feasible and may hold the key to predicting how cortical physiology manifests in NIRS optics 36. NIRS reflects considerable physiological complexity, and model-based physiological interpretation37,38 of NIRS might therefore usefully be used to address influence of other confounding factors such as carbon dioxide tension,39 oxygenation,40 and cerebral metabolic rate 41.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the uncertainties attendant upon parameter estimates from ‘sloppy’ models [ 59 ], it may be unwise to attach too much significance to them in any case. We have previously found that attempts to explain observations through individual parameter fitting can lead to unrealistic predictions [ 72 , 73 ]. Using simpler models should allow for a more coherent overall picture, at the cost of a loss of detail.…”
Section: Discussionmentioning
confidence: 99%